The Effect of COVID-19 Pandemic on the Auditing of Financial Statements- An Analytical Study in Kurdistan Region / Iraq - Omar Haji, Narmin; Falih Jejan, Basima (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
This research aims to examine the effect of the COVID-19 pandemic on the work of external auditors when conducting audits of financial statements in five main areas (professional judgment and skepticism, audit evidence, accounting estimates, going concern, and subsequent events). To achieve the objectives of the study, a questionnaire consisting of 40 paragraphs was distributed to 85 external auditors in the Kurdistan Region and Iraq. The questionnaire was analyzed using the statistical package for social sciences (SPSS) and the linear regression model, and the researcher reached several results, the most important of which is: the reduction of working hours in the offices due to the quarantine procedures imposed by the government or because the external auditor (or one of the employees in the audit office) was infected with the epidemic; a delay in the audit offices in completing the audit work and issuing the audit report; and a statistically significant impact relationship between COVID-19 and the five areas of the external auditing process.